Ecology and the child: Determination of the knowledge level of children aged four to five about concepts of forest and deforestation1. Issue 3 (3rd July 2018) - Ahi, Berat; Balcı, Sibel
ABSTRACT: The purpose of the study is to reveal the knowledge level of pre-school children aged four to five about the concepts of forest and deforestation. The study group of the research consists of 29 children having pre-school education. The data were collected using a standardized open-ended interview technique. Results of the study showed that children have limited knowledge about concepts of forest and deforestation. A significant proportion of children could not define forest ( f = 11) or deforestation ( f = 9). Moreover, although a high number of children stated that the destruction of forests has negative influences on animals but only one child stated it would negatively affect the atmosphere, and only one child stated it would lead to landslides. The children think that the reasons for the destruction of forests are human-induced such as heating, paper production and use of construction materials. No significant correlation was found between the children's knowledge of these two concepts and their age or gender. In light of the findings of the study, it is suggested that ecological concepts should be directly incorporated into pre-school education programmes and that environmental education should be conducted outdoors based on daily life experiences.